TRANSFORMATION OF REGIONAL MILITARY AND POLITICAL PROCESSES UNDER THE INFLUENCE OF THE TALIBAN MOVEMENT (TAMADDUN NURI JURNALI, 2024)
The article provides an in-depth analysis of the reasons for the return to power in Afghanistan in 2021 of the Taliban movement and the prospects for the development of a new state political system. The relevance of the topic is explained by the following: after the Taliban movement gained control of the state, the internal situation in Afghanistan deteriorated, all existing institutions of political power were destroyed, and the exercise of their powers by state authorities was terminated. As a result, the country is facing a comprehensive crisis.